MODEL OF CUSTOMER RE-INTENTION: A PERSPECTIVE OF EXPERIENTIAL MARKETING AND CUSTOMER SATISFACTION - Nabila Aufa Nadya; Syahmardi Yacob; Raja Sarah Fatricia (Journal of Business Studies and Management Review, 2018)
This study aims to examine customer re-invention that supported by experiential marketing through customer satisfaction. The unit of research analyse was the customer of Casa de Alicia Café & Resto. The technique sampling used was purposive sampling. The number of samples used in this study amounted to 105. Analysis of the data used in this study was path analysis using Smart PLS 3.2.7 software. The Goodness of Fit of this study indicated of the model match reliability and validity. The research finding shows that experiential marketing has a significant influence on customer re-intention both directly and indirectly through customer satisfaction.